Penetapan Kadar Besi dan Seng Air Sumur Gali dan Sumur Bor pada Daerah Lenggadai Hilir secara Spektrofotometri Serapan Atom - Anwar, Laila; Fatimah, Cut; Bagas F, Muhammad; Gunawan, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Many people in Lenggadai Hilir Village, Rimba Melintang District, Rokan Hilir Regency, Riau use dug well water and drilled well water as clean water, drinking water and household needs that look cloudy, colored and slightly odorous, possibly containing metals such as Fe and Zn. The content of Fe and Zn metals in clean water has the requirements of the Regulation of the Minister of Health of the Republic of Indonesia Number 416 / Menkes / PER / IX / 1990, namely a maximum of 1.0 mg / l Fe and a maximum of 15 mg / l Zn. The purpose of this study was to determine the levels of Fe and Zn in the water used by the population. This research method is descriptive quantitative. Determination of Fe and Zn levels in water samples in the village was carried out using Atomic Absorption Spectrophotometry (AAS), which were previously destroyed with nitric acid. Before determining the levels, it began with an identification test with several chemical reactions to ensure the presence of Fe and Zn content in the samples. The results showed that all samples tested contained Fe and Zn. All samples of drilled wells contain Fe, the levels of which do not meet the requirements and all Zn samples meet the requirements, from 8 dug well samples there are 6 dug well samples contaminated with Fe, namely dug well 1 (1), dug well 1 (2), dug well 2 (1), dug well 2 (2), dug well 3 (1) and dug well 3 (2). Thus, the water used by the community as clean water and household needs should not be used for household water needs and drinking water before processing and filtering before consumption.